PATTERN OF WATER SUPPLY IN RELATION TO DIFFERENT WATER SOURCES IN METROPOLITAN KANO - Suleiman, Abubakar Hadiza (FUDMA Journal of Sciences, 2020)
The study carried out on pattern of water supply in relation to different water sources in metropolitan Kano was aimed to assess the pattern of water supply in the area. Eight local government areas were found in the area but six local government areas were selected in conducting the research work. The selected local government areas included dala, Fagge, Kano Municipal, Gwale, Tarauni, Nassarawa. The research work was conducted through the following methods of data collection, (questionnaire and interview). Krecjie and morgan sampling techniques was adopted in administering the questionnaire, because it was the best sampling techniques that suited the study. The result of the findings indicated that ground water sources are now the major sources of water used in the study area, pipe borne water was generally inadequate. Dala, Kano Municipal, Fagge and Gwale were the areas mostly affected with scarcity of pipe borne water. Other sources of water for household usage included water from vendors and water supply Tankers. Some sources of water were founded inactive (that is sources of water producing less or no water due to some problems). Most people in the area depend on sachet water as their source of drinking water. Finally, in order to overcome some of the problems of water is their source of drinking water. Finally, in order to overcome some of the problems of water supply it was recommended that there should be alternative sources of power, regular maintenance, train of manpower, and effective management of water supply systems.